Green hotel practice and policy: feedbacks of hotel operators and guests / Mohd Badrul Kamal Yassin and Nazri Marin - Yassin, Mohd Badrul Kamal; Marin, Nazri (2014)
This is a report of a research entitled Green hotel practice & policy: Response by hotel operators and guests. The research consists of findings of inquires obtained purely from the response of hotel operators and guests regarding green hotel practice and policy. Hotel development especially in Malaysia can be seen as blooming rapidly due to increasing demand from tourism sector. Green hotel practices and policy is considered as an alternative and method to uphold the principle of sustainable development, however, it is regarded by most as supplementary especially from the perspective of hotel operators themselves and that guests are indirectly tend to gain similar understanding. Due to such fact, this research paper will reveal the response by both hotelier and guest regarding their commitment and perception towards the policy so as to support a sustainable development ideology. This report consists of five (5) related compositions presented in chapters. Chapter One (I) is the background and introduction, Chapter Two (ii) includes the literature review and its analysis, Chapter Three (III) describes methodology aspects as applied in this research. Chapter Four (IV) and Chapter Five (V) consist of analysis of data and findings and discussion respectively. Chapter Six (VI) elaborates the limitation throughout the study and improvement recommendation and Chapter Seven (VII) concludes the research as a whole and several list of suggestion.